Electrochemical sensor with high-efficiency conductivity and anti-pollution performance as well as preparation method and application of electrochemical sensor
The poor conductivity and non-specific composite were solved by using sodium alginate gel, polyethylene glycol and graphene in electrochemical sensors, and combining Prussian blue analogues and gold nano signal labels. The problem of opposite-sex adsorption achieves efficient conductivity and anti-fouling properties, improves detection sensitivity and simplifies operational processes.
Patent Information
- Application Number
- CN202411571498.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-27
AI Technical Summary
Existing electrochemical sensors face poor conductivity and non-specific adsorption problems when detecting in biological fluids, resulting in weakened signal output and reduced sensitivity, and there are safety hazards when implanted in the body, the operation steps are cumbersome and the reaction time is extended.
Sodium alginate gel, polyethylene glycol and graphene are used to construct a soil-resistant bottom layer, combined with Prussian blue analog and gold nano signal label, and form a sandwich sandwich complex through magnetic beads and cardiac troponin I, fixed on magnetic glassy carbon electrodes On the other hand, build an efficient conductive and anti-fouling electrochemical sensor.
It realizes efficient electronic signal transfer and anti-fouling performance, reduces non-specific adsorption, improves detection sensitivity, simplifies detection steps, shortens reaction time, and provides reliable sensing capabilities for complex biological fluids.
Smart Images

Figure CN119198850A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical sensors, and in particular relates to an electrochemical sensor with both high-efficiency conductivity and anti-fouling performance, and a preparation method and application thereof. Background Art
[0002] In recent years, electrochemical sensors have become a powerful tool for quantitative analysis of biochemical analytes in body fluids, providing a digital basis for dynamic physiological processes for basic research and medical applications, and providing a strong theoretical basis for further construction of portable, wearable and implantable devices, making decentralized POC detection possible. Its inherent advantages of high sensitivity and low cost have laid a potential foundation for the practical application of rapid diagnosis, monitoring, treatment and prognosis of clinical diseases. However, the electrochemical sensors that have been successfully used in testing laboratories have not been fully developed, which is closely related to the following two aspects. First, most biochemical markers are proteins, nucleic acids or small molecules. When interacting with the sensor interface, various molecules with poor conductivity hinder electron transfer and become the main obstacle to weakening the final signal output. Second, when electrochemical sensors are used for molecular detection in complex biological fluids, the various "pollutants" contained therein will inevitably be rapidly and irreversibly adsorbed to the sensor surface. This nonspecific adsorption occupies the signal molecule recognition site, greatly weakening the specificity; at the same time, the surface electron transfer efficiency will also be greatly affected, reducing the sensitivity of the sensor. In severe cases, clumps will form on the surface of implanted sensors in the body, threatening the patient's life safety and causing the sensor to fail, increasing medical costs. At present, the key technology to solve this problem as much as possible mainly relies on pre-treatment of biological samples or adding operation steps to minimize nonspecific adsorption, which leads to cumbersome operation steps and prolonged reaction time. Therefore, it is urgent to develop an electrochemical sensor that can ensure efficient conductivity of the sensor interface and inhibit the adhesion of complex biological molecules, which is crucial for truly entering clinical practical detection applications.
[0003] However, current biosensors only focus on one of these issues, and do not incorporate both of the above issues into the overall design of the sensor, which limits their detection applications in biological fluids. For example, conductive materials are spread on the sensing interface to enable them to conduct electricity quickly; or only anti-fouling compounds that can resist macromolecular proteins and other substances are used for target detection, ignoring the high-efficiency output of the overall electrical signal. Summary of the invention
[0004] In order to solve the problems in the prior art, the present invention provides an electrochemical sensor with both efficient conductivity and anti-fouling properties, and a preparation method and application thereof, so as to achieve the purpose of having efficient electronic signal transfer capability and the ability to resist complex biological samples, and quickly, simply and directly perform highly sensitive detection of biological samples.
[0005] The present invention solves the technical problem by adopting the following technical solutions:
[0006] The present invention aims to provide an electrochemical sensor with both efficient conductivity and anti-fouling properties, comprising an anti-fouling bottom layer, a signal tag and a signal identifier, wherein the anti-fouling bottom layer comprises sodium alginate gel, polyethylene glycol and graphene.
[0007] Furthermore, the signal tag uses Prussian blue analogs and gold nanoparticles, and the signal recognition includes a sandwich complex constructed of magnetic beads, cardiac troponin I and the signal tag.
[0008] A method for preparing an electrochemical sensor having both efficient conductivity and anti-fouling performance comprises the following steps:
[0009] (1) Preparation of antifouling bottom layer: amino polyethylene glycol and graphene solution are added to sodium alginate solution and stirred to form an SPG mixed solution; the SPG mixed solution is dripped onto the surface of the magnetic glassy carbon electrode, and then the magnetic glassy carbon electrode is immersed in a calcium chloride solution for curing, and finally an ion-responsive antifouling coating SPG is formed;
[0010] (2) Preparation of signal tags: CoFePBA@AuNPs were synthesized by synthesizing a cobalt iron Prussian blue analog and a gold nanoparticle solution, respectively. The synthesized cobalt iron Prussian blue analog was ultrasonically dispersed in dd H2O, and then added to the gold nanoparticle solution and mixed and stirred to synthesize CoFePBA@AuNPs.
[0011] (3) Sandwich reaction construction: the magnetic beads-Ab1 and CoFePBA@AuNPs-Ab2 signal probes were incubated with cardiac troponin I to form a double antibody sandwich complex in one step;
[0012] (4) Preparation of electrochemical sensor: The double antibody sandwich complex prepared in (3) is fixed on the surface of the magnetic glassy carbon electrode prepared in (1).
[0013] Furthermore, in (1), before using the magnetic glassy carbon electrode, it is polished with aluminum oxide powder, and the polished magnetic glassy carbon electrode is continuously ultrasonicated in nitric acid and acetone, then rinsed with deionized water, and then blown dry with nitrogen for use.
[0014] Further, in (1), sodium alginate powder was dissolved in 2 mL of deionized water to prepare a 3% sodium alginate solution, 0.04 g of amino polyethylene glycol and 200 μL of a 2 mg / mL graphene solution were added, and the mixture was stirred to form an SPG mixed solution.
[0015] Furthermore, the method for synthesizing the cobalt-iron Prussian blue analog in (2) is as follows: dissolving Co(NO3)2·H2O and C6H5Na3O7·2H2O in ultrapure water to obtain solution A; dissolving potassium ferrocyanide in ultrapure water to obtain solution B; mixing solution A and solution B to obtain a turbid brown liquid, and aging at room temperature; collecting the dark purple precipitate by centrifugation, and then washing it with ddH2O and anhydrous ethanol respectively, and drying it in an incubator overnight.
[0016] Furthermore, the method for synthesizing gold nanoparticles in (2) is to pour HAuCl4 into dd H2O and heat it to boiling under magnetic stirring; add sodium citrate solution to the boiling HAuCl4 solution and stir until the solution turns bright purple.
[0017] Furthermore, in the (3) sandwich reaction construction, 10 μL of magnetic beads-Ab1 and 10 μL of CoFePBA@AuNPs-Ab2 signal probes were incubated with cardiac troponin I suspension or serum at 37 °C for 40 min to directly form a double antibody sandwich complex in one step.
[0018] An electrochemical sensor with both efficient electrical conductivity and anti-fouling properties or a method for preparing an electrochemical sensor with both efficient electrical conductivity and anti-fouling properties is used in biological fluid detection.
[0019] Furthermore, the detection was carried out using differential pulse voltammetry, with the working solution being PBS containing 10 μL H2O2, 0.01M, pH 7.4; the potential range was -0.1 to 0.2 V, the pulse amplitude was 0.3 V, the pulse width was 0.05 s, and the sample width was 0.0167 s.
[0020] The present invention selects natural polysaccharide sodium alginate (SA) with ion response function as the antifouling coating substrate, adds high molecular polymer polyethylene glycol (PEG) and two-dimensional carbon material graphene (Graphene) to give the coating excellent antifouling performance and conductivity, and constructs an electrode sensing interface with both efficient conductivity and antifouling performance. The upper material selects Prussian blue analog gold nanozyme (CoFePBA@AuNPs) with peroxidase activity as a signal probe. Cardiac troponin I (cTnI) is used as a model target protein. When there is a responsive target in the sample, magnetic beads pre-coupled with antibodies are added to the sample to capture and enrich the target protein in large quantities, and the antibody-antigen complex is retained, and then the antibody coupled with CoFePBA@AuNPs is added to form a simple sandwich complex. Then, a magnetic glassy carbon electrode with magnetic properties is directly inserted into the sample to adsorb the formed antigen-antibody complex. After stabilization for one minute, electrochemical detection can be directly performed. Due to the protection of the anti-fouling interface, it can reduce nonspecific adsorption while accelerating the electron transfer rate at the interface, thereby improving the sensitivity of detection.
[0021] Compared with the prior art, the beneficial technical effects of the present invention are:
[0022] 1. The excellent anti-adsorption property of the anti-fouling coating interface of the electrochemical sensor of the present invention can effectively reduce the binding of non-specific substances in complex samples; the combination of high-efficiency conductive materials accelerates the electron transfer rate on the electrode surface, which is beneficial to improving the sensitivity of the sensor.
[0023] 2. The present invention does not require pretreatment of the sample, and can directly achieve efficient and rapid detection in one step through the magnetic attraction of the magnetic glassy carbon electrode, thereby reducing the number of reaction steps and shortening the reaction time.
[0024] 3. The present invention constructs a universal antifouling electrochemical coating that can be used in different application scenarios and provides a new solution for the reliable and long-term sensing of complex biological fluids.
[0025] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above contents of the present invention and its objectives, features and advantages more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a diagram of the electrochemical sensor preparation method and detection principle of the present invention.
[0027] Figure 2 This is a scanning electron microscope result image during the construction process of the anti-fouling coating in Experimental Example 1 of the present invention.
[0028] Figure 3 This is a test diagram of the contact angle of the lower layer water for verifying the anti-fouling in Experimental Example 2 of the present invention.
[0029] Figure 4 This is a test diagram of the adsorption of the anti-fouling coating on actual biological samples in Experimental Example 3 of the present invention.
[0030] Figure 5 This is a diagram of the electrochemical results for verifying the feasibility of the electrochemical sensor in detecting the target protein in the actual sample in Experimental Example 4 of the present invention.
[0031] Figure 6 This is a linear fitting result diagram of the verification electrochemical sensor detecting the target protein in the actual sample in Experimental Example 5 of the present invention. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0033] In addition, unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0034] An electrochemical sensor with both efficient conductivity and anti-fouling properties mainly includes three components: an anti-fouling bottom layer, a signal recognition part, and a signal label part. The anti-fouling bottom layer includes ion-responsive SA gel, PEG with anti-fouling function, and graphene with good conductivity. The ion exchange reaction between CaCl2 and SA forms a cross-linked network structure, which accelerates and solidifies the agglutination process of the bottom gel, and finally forms SPG gel. The signal label part uses CoFePBA@AuNPs with efficient peroxidase ability as the signal output part of the overall reaction. The signal recognition part includes a sandwich method design. When the target protein in the sample is bound by the magnetic bead-coupled antibody, it reacts with the CoFePBA@AuNPs coupled with the secondary antibody to form a sandwich structure. Under the interaction between the magnetic glassy carbon electrode and the magnetic beads, the formed sandwich complex can be stabilized on the electrode surface within one minute for the subsequent electrochemical test.
[0035] Preparation method of an electrochemical sensor with both high-efficiency conductivity and anti-fouling performance and detection of cardiac troponin I
[0036] 1 Materials and methods
[0037] 1.1 Materials
[0038] Sodium alginate (SA) and calcium chloride (CaCl2) were purchased from McLean, amino polyethylene glycol (PEG-NH2) was purchased from Sigma-Aldrich, and carboxylated graphene (Graphene-COOH) was purchased from Xianfeng Nano.
[0039] 1.2 Testing instruments
[0040] The CV and EIS signals of the reaction were recorded by using Donghua electrochemical workstation. The DPV value of the reaction was recorded by Chenhua CHI600. Confocal microscopy imaging was performed on a confocal laser scanning microscope (Zeiss, Germany).
[0041] 1.3 Detection principle
[0042] The natural polysaccharide sodium alginate (SA) with ion response function was selected as the antifouling coating substrate, and the high molecular weight polymer polyethylene glycol (PEG) and the two-dimensional carbon material graphene (Graphene) were added to give the coating excellent antifouling performance and conductivity. The ion exchange reaction between CaCl2 and SA was used to form a cross-linked network gel structure after liquid solidification for 1 minute, and an electrode sensing interface SPG with both efficient conductivity and antifouling performance was constructed. The two-dimensional network constructed by the gel provides electron conduction, and graphene has good conductivity. In addition, the traditional antifouling material PEG achieves excellent antifouling effect. The upper layer material selected Prussian blue analogs with peroxidase and gold nanoparticles (CoFePBA@AuNPs) as signal probes. Cardiac troponin I (cTnI) was used as a model target protein. When the responsive target existed in the sample, the magnetic beads pre-coupled with antibodies were added to the sample to capture and enrich the target protein in large quantities, and the antibody-antigen complex was retained, and then the antibody coupled with CoFePBA@AuNPs was added to form a simple sandwich complex. Then, the magnetic glassy carbon electrode is directly inserted into the sample to adsorb the formed antigen-antibody complex. After stabilization for one minute, electrochemical detection can be performed directly. Due to the protection of the anti-fouling interface, it can reduce nonspecific adsorption while accelerating the electron transfer rate at the interface, thereby improving the sensitivity of detection.
[0043] 1.4 Preparation and reaction
[0044] (1) Preparation of anti-fouling base layer
[0045] The magnetic glassy carbon electrode (MGCE, 3 mm in diameter) was polished with alumina powder (0.3 μm and 0.05 μm) for 10 min and then washed with deionized water. The polished electrode was continuously sonicated in nitric acid and acetone (1:1), then thoroughly rinsed with deionized water and dried with nitrogen for later use. SA powder was dissolved in 2 mL of deionized water to prepare a 3% SA solution, 0.04 g of PEG-NH2 and 200 μL of graphene solution (2 mg / mL) were added, and stirred evenly to form an SPG mixed solution. 10 μL of SPG solution was added to the surface of the magnetic glassy carbon electrode with a micropipette gun, and 9 μL was sucked away to form a thin SPG interface on the surface. The magnetic glassy carbon electrode was inverted and immersed in a CaCl2 solution (0.333 mol / L) for curing for 1 min, and finally an ion-responsive antifouling coating SPG was formed.
[0046] (2) Signal tag preparation
[0047] a. Synthesis of CoFePBA: Dissolve 436.2 mg Co(NO3)2·H2O (0.6 M) and 441.2 mg C6H5Na3O7·2H2O (0.6 M) in 50 mL ultrapure water to obtain solution A. Dissolve potassium ferrocyanide (329.3 mg, 0.4 M) in 50 mL ultrapure water to obtain solution B. Mix solution A and solution B quickly and react for 5 min to obtain a turbid brown liquid, which is aged at room temperature for 24 h. Centrifuge at 8000 rpm for 5 min to collect the dark purple precipitate, then wash it 3 times with dd H2O and anhydrous ethanol respectively, and dry it in an incubator at 60°C overnight.
[0048] b. Synthesis of AuNPs: Pour 1 mL of HAuCl4 (1%) into 99 mL of dd H2O and heat to boiling under magnetic stirring. Next, add 1.5 mL of 1% sodium citrate solution to the boiling HAuCl4 solution and stir for 10 minutes until the solution turns bright purple.
[0049] c. Synthesis of CoFePBA@AuNPs: The CoFePBA synthesized above was ultrasonically dispersed in dd H2O to prepare 1 mg / ml CoFePBA. 1 ml was added to 9 ml of the above AuNPs solution and stirred at room temperature for 2 h.
[0050] (3) Sandwich reaction construction
[0051] Subsequently, 10 μL of the prepared magnetic beads-Ab1 and 10 μL of the CoFePBA@AuNPs-Ab2 signal probe were incubated with the cTnI suspension or serum at 37 °C for 40 min to directly form a double antibody sandwich complex in one step.
[0052] (4) Preparation of electrochemical sensors
[0053] Finally, due to the special properties of the magnetic glassy carbon electrode, the sandwich complex can be fixed on the MGCE surface within 1 min.
[0054] 1.5 Detection of cardiac troponin I
[0055] Electrochemical measurements were performed using differential pulse voltammetry (DPV) in PBS containing 10 μL H2O2, 0.01 M, pH 7.4, with a potential range of -0.1 to 0.2 V, a pulse amplitude of 0.3 V, a pulse width of 0.05 s, and a sample width of 0.0167 s.
[0056] Experimental Example 1: Verification of the successful construction of antifouling coating
[0057] like Figure 2 As shown in the figure, the correctness of SPG construction was confirmed by scanning electron microscopy (SEM) analysis: after SA was coated on the electrode surface, the microscopic results showed that it was evenly distributed and the surface was flat. Secondly, amino PEG was added, and most of its -NH2 groups reacted with the -COOH of SA to form a cross-linked support layer, so there was no obvious agglomeration on the surface of the SA / PEG coating. After that, the carboxylated Graphene reacted with SP through simple physical doping and chemical bonding, and was evenly coated on the electrode surface as particles with a particle size of 100nm, finally forming SA / PEG / Graphene, showing the same film-like coating as before.
[0058] Experimental Example 2: Verifying the anti-fouling performance of the lower layer
[0059] like Figure 3 As shown in the figure, the water contact angle test verified that compared with the bare electrode, the water contact angle of the SPG gel coating was significantly reduced, it has good hydrophilicity, and can exert excellent anti-fouling ability.
[0060] Experimental Example 3: Verification of the anti-adsorption ability of the anti-fouling coating in different serum dilutions
[0061] The antifouling performance of the constructed antifouling lower layer was investigated in diluted normal human serum at concentrations of 0, 10%, 20%, 40%, 60%, 80%, and 100%. Figure 4 It can be seen that the current signal of the bare MGCE is significantly reduced after incubation with complex biological samples, because the proteins or other contaminants in the fresh serum of normal people are adsorbed to the electrode surface, resulting in a signal reduction. The SPG coating we constructed always maintains most of the initial current, and its inhibition is minimal, which is 25% in serum, while the current of the bare electrode drops significantly, which is 83%, indicating that the anti-fouling lower layer we constructed has a good ability to resist contamination in actual samples, providing a basis for further application in sensor detection.
[0062] Experimental Example 4: Verification of the feasibility of electrochemical sensor detection of cTnI
[0063] The feasibility of the sensor was verified directly using collected clinical samples. Figure 5 It can be seen that the anti-fouling electrochemical sensor we constructed can be successfully used in the detection of actual clinical samples.
[0064] Experimental Example 5: Linearity Verification of Electrochemical Sensor
[0065] like Figure 6 As shown, in the range of 0.01 to 100 ng mL -1 In the range of 2.5 Å, the current response of the electrochemical sensor showed a good linear relationship with the logarithm of the cTnI concentration.
[0066] The present invention provides an electrochemical sensor that can directly detect target molecules in actual clinical biological samples. The present invention innovatively proposes a sensing strategy that combines efficient conductivity and anti-fouling performance. The above strategy is achieved by preparing a SA / PEG / Graphene (SPG) anti-fouling coating and utilizing the high conductivity of Graphene and the anti-fouling ability of the SA / PEG layer. At the same time, combined with the magnetically oriented adsorption stability characteristics of the magnetic glassy carbon electrode, there is no need to perform complex separation steps on the sample, thereby achieving a homogeneous sensitive and rapid detection of the target analyte, achieving the purpose of "two-pronged approach".
[0067] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0068] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. An electrochemical sensor having both high-efficiency conductivity and anti-fouling performance, characterized in that: It includes an anti-fouling bottom layer, a signal label and a signal recognition, and the anti-fouling bottom layer includes sodium alginate gel, polyethylene glycol and graphene.
2. An electrochemical sensor having both efficient electrical conductivity and anti-fouling properties as claimed in claim 1, characterized in that: The signal tag uses Prussian blue analogs and gold nanoparticles, and the signal recognition includes a sandwich complex constructed of magnetic beads, cardiac troponin I and the signal tag.
3. A method for preparing an electrochemical sensor having both efficient conductivity and anti-fouling properties as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of antifouling bottom layer: Add amino polyethylene glycol and graphene solution to the sodium alginate solution and stir evenly to form an SPG mixed solution; The SPG mixed solution is dropped onto the surface of the magnetic glassy carbon electrode, and then the magnetic glassy carbon electrode is immersed in a calcium chloride solution for solidification, and finally an ion-responsive antifouling coating SPG is formed; (2) Preparation of signal tags: CoFePBA@AuNPs were synthesized by synthesizing a cobalt iron Prussian blue analog and a gold nanoparticle solution, respectively. The synthesized cobalt iron Prussian blue analog was ultrasonically dispersed in dd H2O, and then added to the gold nanoparticle solution and mixed and stirred to synthesize CoFePBA@AuNPs. (3) Sandwich reaction construction: the magnetic beads-Ab1 and CoFePBA@AuNPs-Ab2 signal probes were incubated with cardiac troponin I to form a double antibody sandwich complex in one step; (4) Preparation of electrochemical sensor: The double antibody sandwich complex prepared in (3) is fixed on the surface of the magnetic glassy carbon electrode prepared in (1).
4. A method for preparing an electrochemical sensor having both efficient conductivity and anti-fouling performance as claimed in claim 3, characterized in that: In (1), before using the magnetic glassy carbon electrode, it is polished with aluminum oxide powder. The polished magnetic glassy carbon electrode is continuously ultrasonicated in nitric acid and acetone, then rinsed with deionized water, and then blown dry with nitrogen for use.
5. A method for preparing an electrochemical sensor having both efficient conductivity and anti-fouling performance as claimed in claim 4, characterized in that: (1), sodium alginate powder was dissolved in 2 mL of deionized water to prepare a 3% sodium alginate solution, 0.04 g of amino polyethylene glycol and 200 μL of a 2 mg / mL graphene solution were added, and the mixture was stirred to form an SPG mixed solution.
6. A method for preparing an electrochemical sensor having both efficient conductivity and anti-fouling properties as claimed in claim 3, characterized in that: (2) The method for synthesizing the cobalt-iron Prussian blue analogue is as follows: dissolving Co(NO3)2·H2O and C6H5Na3O7·2H2O in ultrapure water to obtain solution A; dissolving potassium ferrocyanide in ultrapure water to obtain solution B; mixing solution A and solution B to obtain a turbid brown liquid, and aging at room temperature; collecting a dark purple precipitate by centrifugation, and then washing it with dd H2O and anhydrous ethanol, respectively, and drying it in an incubator overnight.
7. A method for preparing an electrochemical sensor having both efficient conductivity and anti-fouling properties as claimed in claim 6, characterized in that: The method for synthesizing gold nanoparticles in (2) is to pour HAuCl4 into dd H2O and heat it to boiling under magnetic stirring; add sodium citrate solution to the boiling HAuCl4 solution and stir until the solution turns bright purple.
8. A method for preparing an electrochemical sensor having both efficient conductivity and anti-fouling properties as claimed in claim 3, characterized in that: (3) In the sandwich reaction construction, 10 μL of magnetic beads-Ab1 and 10 μL of CoFePBA@AuNPs-Ab2 signal probes were incubated with cardiac troponin I suspension or serum at 37 °C for 40 min to directly form a double antibody sandwich complex in one step.
9. Application of the electrochemical sensor with both efficient conductivity and anti-fouling performance as claimed in claim 1 or 2 or the method for preparing the electrochemical sensor with both efficient conductivity and anti-fouling performance as claimed in any one of claims 3 to 8 in biological fluid detection.
10. The use according to claim 9, characterized in that: The detection was carried out by differential pulse voltammetry, and the working solution was PBS containing 10 μL H2O2, 0.01M, pH 7.4; the potential range was -0.1 to 0.2 V, the pulse amplitude was 0.3 V, the pulse width was 0.05 s, and the sample width was 0.0167 s.
Citation Information
Patent Citations
Method for rapidly detecting impedance of escherichia coli in food based on nano magnetic beads
CN113311029A
Anti-pollution electrochemical immunosensor based on PEG-polypeptide conjugate as well as preparation method and application of anti-pollution electrochemical immunosensor
CN116008370A
Conductive anti-pollution working electrode, reaction system and application
CN118731136A
